2022
DOI: 10.1039/d2na00279e
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive textiles made from silver nanoparticle-filled brown cotton fibers

Abstract: Filling nanomaterials into fibers can create new functions or modify the existing properties. However, as nanocomposite formation for natural cellulosic fibers has been challenging, little information is available on how...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This unique functionality was attributed to the presence of noncellulosic constituents within raw cotton fibers, specifically pectin, fatty alcohols, sugars, hemicellulose, and proteins. These noncellulosic constituents are plentiful in electron-rich functional groups, enabling them to establish electrostatic interactions with silver cations and convert silver ions into silver atoms. ,,, For instance, the oxidation of hydroxyl groups in pectin results in the reduction of silver ions through a series of reactions involving duplicative acetaldehyde oxidation following cyclo-oxo tautomerization . Similarly, galactose-containing vicinal diols in hemicellulose undergo oxidation to form a dialdehyde product, leading to the autoreduction of silver ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This unique functionality was attributed to the presence of noncellulosic constituents within raw cotton fibers, specifically pectin, fatty alcohols, sugars, hemicellulose, and proteins. These noncellulosic constituents are plentiful in electron-rich functional groups, enabling them to establish electrostatic interactions with silver cations and convert silver ions into silver atoms. ,,, For instance, the oxidation of hydroxyl groups in pectin results in the reduction of silver ions through a series of reactions involving duplicative acetaldehyde oxidation following cyclo-oxo tautomerization . Similarly, galactose-containing vicinal diols in hemicellulose undergo oxidation to form a dialdehyde product, leading to the autoreduction of silver ions.…”
Section: Resultsmentioning
confidence: 99%
“…The sample was in contact with the soil through the mesh openings. The study consisted of two treatments (treated and untreated), five excavation times (2,4,7,12, and 16 weeks after burial), and four replicates. The fabrics were excavated at their respective excavation times, air-dried at room temperature, and lightly brushed to remove large soil particles.…”
Section: Soil Burialmentioning
confidence: 99%
“…The noncellulosic constituents of cotton gin waste were expected to have the ability to act as reducing agents, converting silver ions into silver atoms. Previous studies have shown that the noncellulosic constituents found in the primary cell wall of raw cotton fiber, such as pectin, protein, and sugars, and condensed tannins present in brown cotton fiber are efficient in reducing silver ions to produce silver nanoparticles. The abundance of various noncellulosic constituents in cotton gin waste is expected to enhance the efficiency of reduction reactions. Figure shows the chemical structures of the selected noncellulosic constituentshemicellulose and ligninand their corresponding reduction reaction schemes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research found that the internal formation of Ag NPs within cotton bers slightly reinforced the tensile strength of the ber 47 and increased the thermal sensitivity of cotton ber during thermal decomposition and post heat treatment. 48 Fig. 8a and b show the high-resolution TEM images of Ag NPs in the primary cell wall, and Fig.…”
Section: Resultsmentioning
confidence: 99%